1993
DOI: 10.1007/bf00356030
|View full text |Cite
|
Sign up to set email alerts
|

The replication behavior of Saccharomyces cerevisiae DNA in human cells

Abstract: We studied the replication of random genomic DNA fragments from Saccharomyces cerevisiae in a long-term assay in human cells. Plasmids carrying large yeast DNA fragments were able to replicate autonomously in human cells. Efficiency of replication of yeast DNA fragments was comparable to that of similarly sized human DNA fragments and better than that of bacterial DNA. This result suggests that yeast genomic DNA contains sequence information needed for replication in human cells. To examine whether DNA replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Replication initiates in these recombinants at multiple locations both on the vector and insert sequences . These results and subsequent studies (Caddle and Calos, 1992;Tran et al, 1993) convincingly showed that a relaxed sequence specificity for initiation on plasmids is not a unique feature of amphibian eggs.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Replication initiates in these recombinants at multiple locations both on the vector and insert sequences . These results and subsequent studies (Caddle and Calos, 1992;Tran et al, 1993) convincingly showed that a relaxed sequence specificity for initiation on plasmids is not a unique feature of amphibian eggs.…”
Section: Introductionsupporting
confidence: 52%
“…In the frog Xenopus laevis, any plasmid molecule injected into unfertilized eggs replicates under cell cycle control with an efficiency which depends only upon the size of the plasmid and not on the presence of any particular DNA sequence (Harland and Laskey, 1980;Mechali and Kearsey, 1984). These results and subsequent studies (Caddle and Calos, 1992;Tran et al, 1993) convincingly showed that a relaxed sequence specificity for initiation on plasmids is not a unique feature of amphibian eggs. However, the relevance of these findings for other cell types was not obvious, because amphibian eggs are specialized cells primed for the very rapid cell cycles that follow fertilization.…”
Section: Oxford University Pressmentioning
confidence: 88%
“…The yeast shuttle plasmid pYES2 also replicated in HeLa cells (Figure 3B). This plasmid does not contain a mammalian replication origin, and is not capable of long-term replication in mammalian cells (37). …”
Section: Resultsmentioning
confidence: 99%
“…The 2-D gel technique does not have sufficient resolution to determine whether initiation occurs at a single site or is dispersed over a small region in these origins. These results put S. pombe in a class with the budding yeast S. cerevisiae, rather than with animal cells such as Xenopus and human cells, for which 2-D gel analysis has demonstrated that initiation of autonomous replication appears to occur over a large area (5,22,25,26,28,47).…”
Section: Discussionmentioning
confidence: 99%